Lactate threshold does not influence metabolic responses during exercise in cyclists - Bentley, D. J.; McNaughton, L. R.; Roberts, S.; Vleck, V. E.; Fairbanks, L.; Marinaki, T. (International Journal of Sports Medicine, 2007)
The purpose of this study was to compare plasma markers of metabolic stress and other physiological parameters during prolonged endurance exercise of different intensity in trained subjects possessing a "high" or "low" lactate threshold (LT) expressed as a percentage (%) of peak power output (PPO). Fifteen trained male cyclists completed an incremental exercise test for determination of PPO and the LT (% PPO). Each subject then completed a 90-min and 20-min exercise trial at an intensity representing 75 and 85 % of PPO, respectively. Blood lactate (La), as well as plasma hypoxanthine (Hx) and uric acid (UA) were measured during each exercise trial. The responses in two groups, one (n = 8) with a LT ~ 65 % PPO (LTlow), the other group (n = 7) with a LT ~ 75 % (LThigh) (p < 0.01), were then compared. With the exception of UA, La and Hx increased significantly (p < 0.01) throughout each exercise trial compared to rest. However, there were no significant differences in each trial between the two groups of cyclists. There were also no significant differences in the other physiological parameters in each exercise trial between the subjects in LTlow and LThigh. This study demonstrates that in trained cyclists homogeneous in terms of PPO, plasma markers of metabolic demand during prolonged exercise are not influenced by the LT when measured in an incremental exercise test.